PENYULUHAN DAN PEMBUATAN LEGAL DRAFTING AKAD MUDHARABAH PETERNAKAN SAPI DI DESA BATTAL KECAMATAN PANJI KABUPATEN SITUBONDO - Musram Doso; Syaiful Bakri; Wildatul Mukammilah (LPPI UMN AL WASHLIYAH, 2024)
In the context of Indonesian civil law, the mudharabah contract is a form of cooperation agreement in the business world that is widely used, especially in business sectors involving investment and profit sharing. Disputes often occur between the parties (who enter into a mudharabah contract) when one of them does something that is not in accordance with the initial agreement (default), usually a matter of time, the difficulty in resolving this case is that there is no strong evidence and witnesses for the legal basis. Battal Village, Panji District, Situbondo Regency, is an area that has potential in the plantation and agriculture sectors. Plantations and agriculture in this area include various commodities, such as mangoes, sugar cane, corn and rice which require careful financing and management. In this context, strategy means planning steps regularly and comprehensively to achieve the desired goals. This includes thinking far ahead, making clear plans, and implementing them systematically over a specified period of time. Counseling on the creation of legal drafting of the Mudharabah contract showed very positive results. The success of the counseling program is influenced by several supporting factors such as the quality of the material, presenters, interactive teaching methods, visual aids, and increased participant motivation. Addressing these barriers is important to improve the effectiveness of future extension and ensure better application of knowledge in practice.